Characterization of Induced Pluripotent Stem Cells from Human Epidermal Melanocytes by Transduction with Two Combinations of Transcription Factors - Cheng, Sai; Li, Di; Zhang, Ru-Zhi; Zhu, Jing; Wang, Li; Liu, Qi; Chen, Ren-He; Liu, Xiao-Ming (Current Gene Therapy, 2019)
Objective: In order to generate induced Pluripotent Stem Cells (iPSCs) more efficiently, it is crucial to identify somatic cells that are easily accessible and possibly require fewer factors for conversion into iPSCs. Methods: Human epidermal melanocytes were transduced with lentiviral vectors carrying 3 transcription factors (OCT-4, KLF-4 and c-MYC, 3F) or 4 transcription factors (OCT-4, KLF-4, c-MYC and SOX-2, 4F). Once the clones had formed, assays related to stem cell pluripotency, including alkaline phosphatase staining, DNA methylation levels, expression of stem cell markers and ultrastructure analysis were carried out. The iPSCs obtained were then induced to differentiate into the cells representing the three embryonic layers in vitro. Results: Seven days after the transduction of epidermal melanocytes with 3F or 4F, clones were formed that were positive for alkaline phosphatase staining. Fluorescent staining with antibodies against OCT-4 and SOX-2 was strongly positive, and the cells showed a high nucleus-cytoplasm ratio and active karyokinesis. No melanosomes were found in the cytoplasm by ultrastructural analysis. There were obvious differences in DNA methylation levels between the cloned cells and their parental cells. However, there was not a significant difference between 3F or 4F transfected clonal cells. Meanwhile, the iPSCs successfully differentiated into the three germ layer cells in vitro. Conclusion: Human epidermal melanocytes do not require ectopic SOX-2 expression for conversion into iPSCs, and may serve as an alternative source for deriving patient-specific iPSCs with fewer genetic elements.
Keywords: multipotential